Plant-parasitic nematodes associated with tropical pastures in Colombia - Stanton, J.M.; Siddiqi, MR; Lenné, Jillian M. (1989)
A survey of three regions of Colombia revealed a total of 31 species of plant-parasitic nematodes associated with tropical pasture legumes and grasses. Seventeen of these nematode species had not been recorded previously in Colombia. There also are 120 newly reported associations of plant-parasitic nematodes on tropical pasture legumes and grasses. The nematode species found most commonly and abundantly were Helicotylenchus spp., Pratylenchus spp., especially P. brachyurus, Monotrichodorus monohystera and Xiphinema spp. The plant species surveyed were Andropogon gayanus, Arachis pintoi, Brachiaria spp., Centrosema spp., Desmodium spp., Hyparrhenia rufa, Melinis sp., Pueraria phaseoloides, Stylosanthes spp., and Zornia sp.